IMPLEMENTASI MEDIA KOMIK DIGITAL DALAM MENINGKATKAN MOTIVASI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SISWA KELAS X SMA NEGERI 1 MALANG - Sukaina Zen; Lia Nur Atiqoh Bela Dina; Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
From the results of observations at SMAN 1 Malang, it was found that 1) students feelbored when learning using ppt, because there are too many writings that must be readby students, 2) semi-online and offline learning makes students lazy with media that istoo long, 3) Student learning outcomes are low below the KKM, which is 70. Therefore,researchers implement digital comic learning media to increase student motivation inIslamic religious education subjects. This research was conducted on students of classX MIPA 2 SMA Negeri 1 Malang. This research uses Kurt Lewin's class action researchmodel. This data search used 5 methods, namely observation, student interviews,written tests, questionnaires and documentation. The results of this study indicate thatbased on the results of observations the average value obtained from the first cycle is4.4. From the results of student learning has increased in the first cycle this can beproven with an average percentage of 78.22%. Meanwhile, from the results of thestudent motivation questionnaire assessment in the implementation of the first cycle,the average score of the student motivation percentage was 83%.